Brain Gymnastics Video Media to Increase Learning Concentration for Third Grade Students - Putu Juwita Cahyanti; Kadek Suranata; Kadek Yudiana (Universitas Pendidikan Ganesha, 2024)
This study was motivated by the low level of learning concentration among third-grade elementary students, as identified through the initial results of the Grid Concentration Test, which showed that most students were categorized as